Evaluation of the Cataract Surgery 2018 Survey in Terms of Achieving Refractive Cataract Surgery Targets - İzzet Can; Tamer Takmaz; Akif Özdamar; Ümit Kamış; Yonca Aydın Akova; Osman Şevki Arslan; Mehmet Baykara; Kazım Devranoğlu; Üzeyir Günenç; Fatih Mehmet Mutlu; Altan Atakan Özcan; Emrullah Taşındı (Türk Oftalmoloji Dergisi, 2021)

(untitled)
Objectives:The aim of this study was to show at what rate the technological equipment used in cataract surgery by Turkish ophthalmologists and their knowledge are reflected in practice and how up to date they are.Materials and Methods:A questionnaire conducted using SurveyMonkey was used to evaluate the answers to 17 questions from 823 members of the Turkish Ophthalmological Association. Results were evaluated in subgroups according to the participants’ age, occupational status, institutions, and whether they conducted relevant academic activities, and the data were compared as inadequate, standard, and contemporary approaches according to the determined criteria.Results:Optical biometry devices were used at rates of 77.7% and 67.3% for intraocular lens (IOL) power calculations and keratometric measurements in preparation for cataract surgery, respectively. For IOL power calculation, third-generation formulas, especially the SRK-T, were used most commonly (46.2%), followed by second-generation formulas (21.9%), and fourth/fifth-generation formulas and multiple evaluations for different axial lengths (31.9%). The most common incision size was 2.8 mm (51.6%), while the percentage of 2.2 mm and shorter incisions considered to be neutral in terms of surgically induced astigmatism was 18.8%. When selecting incision location, approaches to reduce corneal astigmatism were reported by 28.9%, neutral approaches by 26.2%, and insensitive approaches by 44.9%. Additionally, 55.6% of participants never implanted toric IOLs and 50.7% did not use presbyopia-correcting IOLs. The proportion of surgeons who have experience with femtosecond laser-assisted cataract surgery was 10.3% and the rate of intracameral antibiotic injection at the end of the operation was 89.4%.Conclusion:It was seen that Turkish cataract surgeons were able to use high technology for surgical preparation and surgery at high rates, but this was not reflected in practice at same rate in terms of achieving contemporary standards of refractive cataract surgery.